STRATEGI PENGEMBANGAN PRODUK UNGGULAN LURIK DENGAN MENGGUNAKAN ANALISIS SWOT (STUDI KASUS PADA INDUSTRI LURIK ATBM DI KABUPATEN KLATEN) - Ahmad Firman; Rismawati Rismawati (Jurnal Bisnis dan Kewirausahaan, 2019)
Klaten is a Regency that promote the economy development through small and Medium Businesses (SMEs), where one of them was an attempt in the fields of textile, namely woven fabric striated. Characteristics of making of the striated weaving in the region are striated woven fabric made using traditional tools or often called ATBM (Loom not machines). This research aims to determine the industry's development strategy as superior product areas in the Klaten Regency. The location of the research products are striated in Klaten. this research Approach uses qualitative descriptive.Method of data collection using the interview and Focus Group Discussion (FGD). While data analysis using SWOT analysis. The results of this study indicate that superior product development strategy of weaving striated in Klaten Regency with SWOT analysis retrieved 7 4 power factor of factors of weakness, 9 factors odds and threat factors 9.Next the necessary strategies to enhance strengths and minimize weaknesses, exploit opportunities or opportunities as well as minimizing threats, so that it can formulate strategies in 12 developing a superior product from the Center a small industry of Striated ATBM in Klaten Regency in order to increase its competitiveness.